2016
DOI: 10.1089/sur.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte and Platelet to Lymphocyte Ratios Are More Effective than the Fournier's Gangrene Severity Index for Predicting Poor Prognosis in Fournier's Gangrene

Abstract: The Fournier's Gangrene Severity Index scoring system was not associated with determining poor prognosis, however, high NLR and high PLR were associated with predictors of mortality in patients with Fournier's gangrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…Escherichia coli was the most frequently identified pathogen (14.4%), followed by retrospective study and found that high NLR and high PLR were independent prognostic factors for poor prognosis from Fournier's gangrene. 24 Wong et al developed the laboratory risk indicator for NF (LRINEC) score in 2004, which is widely accepted for risk stratification in NF. 25 Using white blood cell count, hemoglobin, sodium, glucose, serum creatinine and serum C-reactive protein they developed a scoring system for the likelihood of NF on admission in the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli was the most frequently identified pathogen (14.4%), followed by retrospective study and found that high NLR and high PLR were independent prognostic factors for poor prognosis from Fournier's gangrene. 24 Wong et al developed the laboratory risk indicator for NF (LRINEC) score in 2004, which is widely accepted for risk stratification in NF. 25 Using white blood cell count, hemoglobin, sodium, glucose, serum creatinine and serum C-reactive protein they developed a scoring system for the likelihood of NF on admission in the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…73 The neutrophil-lymphocyte ratio (NLR), plateletlymphocyte ratio (PLR), and monocyte-lymphocyte ratio (MLR) are newer validated clinical scoring tools with wide use for predicting disease severity in many inflammatory and infectious conditions, recently utilized for FG as well. 74,75 Yim et al (2016) determined that admission labs demonstrating PLR> 140 and NLR >8 were associated with 11.6 and 4.66fold increased odds of mortality, respectively. 75 Higher neutrophil-lymphocyte and platelet-lymphocyte ratios are indicative of worse prognosis.…”
Section: Laboratory Investigations and Clinical Scoring Systemsmentioning
confidence: 99%
“…74,75 Yim et al (2016) determined that admission labs demonstrating PLR> 140 and NLR >8 were associated with 11.6 and 4.66fold increased odds of mortality, respectively. 75 Higher neutrophil-lymphocyte and platelet-lymphocyte ratios are indicative of worse prognosis. Retrospective comparison of the FGSI against NLR and PLR in patients with FG found higher NLR and PLR values correlated with higher mortality, including in…”
Section: Laboratory Investigations and Clinical Scoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used to clean and disinfect wounds in the 20th century. 4 Dakin's solution is effective against a wide range of aerobic and anaerobic organisms and fungi, including organisms that are highly resistant to systemic antibiotics. 5 In this study, we aimed to show potentially efficient of Dakin's solution on wound healing, reoperation rate and mortality on FG.…”
Section: Introductionmentioning
confidence: 99%